Distributed appliction with microsoft visual C1+ 6.0 MSCD training kit - Microsoft Corporation (New Delhi Prentice Hall of India, 2001)
Real world developer training for results on the job and on the exam. Build real world programming skills-with the official Microsoft training kit. Work through a system of self-placed lessons and hands on laws to learn how to create components for distri
Keywords: Distributed database; C++ (Computer programm language)